Offshore pipelines crossing active seismic faults - Τριμιντζίου, Μαρία (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών, 2015)
Nowadays, the exploitation of hydrocarbons reserves in deep seas and oceans, in combination with the need to transport hydrocarbons among countries, has made the design, construction and operation of offshore pipelines very significant. Under this perspective, it is evident that many more offshore pipelines are expected to be constructed in the near future and in particular in the wider Mediterranean region. Given the fact that offshore pipelines are crossing extended areas, they may face a variety of geo-hazards that cause substantial permanent ground deformations and potentially threaten the integrity of the pipeline. The present study focuses on the impact of permanent ground deformations induced by active seismic faults on offshore pipelines. For this purpose, a numerical simulation (through finite-element modeling and strain-based criteria) is made, in order to study the distress of offshore pipelines subjected to PGDs induced by active normal and reverse seismic faults at the seabed. Factors, such as the geometrical properties of the fault, the mechanical properties of the ruptured soil formations, and the pipeline characteristics, are examined. Beginning with an extended introduction to the subject, by presenting some general aspects of offshore pipelines and marine geo-hazards, the problem under investigation and the motivation of the study are explained. Subsequently the geo-hazard of seismic faults is further analyzed as well as the special seismic characteristics of the Mediterranean region. After a literature review on similar researches, a validation of the numerical model, developed in the present study, is performed, through the comparison of the numerical results with the analytical predictions of another study. Having validated the numerical model, a range of critical parameters is examined and their impact on the pipeline is presented. After some interesting conclusions regarding the seismic vulnerability of offshore pipelines, potential cost-effective mitigation measures are proposed taking into account constructability issues.